Additional records of the genus \(Ceresium\) Newman, 1842 (Coleoptera: Cerambycidae: Cerambycinae: Callidiopini) from Vietnam - Quynh Nga, Cao Thi (Academia Journal of Biology, 2023)
The paper listed 12 species of the genus Ceresium belonging to the tribe Callidiopini from Vietnam. Of the total 12 species, there are 4 species additional recorded for Vietnam’s fauna, viz. Ceresium furtivum Pascoe, 1869; Ceresium nilgiriense Gahan, 1906; Ceresium quadrimaculatum Gahan, 1900; Ceresium rouyeri Pic, 1943. Descriptions of four newly recorded species and a key to species of the genus Ceresium from Vietnam were provided. Notes on the distribution of all species occurring in Vietnam are also given.